Pengaruh Manajemen Modal Kerja Dan Rasio Aktivitas Terhadap Profitabilitas Pada Industri Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2016 – 2020 (Studi Kasus Pada PT. Indofood Sukses Makmur) - Khoirul Fikri Nasution; Miftahuddin Miftahuddin; Ahmad Prayudi (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2022)
This study aims to determine and analyze the effect of Working Capital on Profitability at PT. Indofood Sukses Makmur 2016-2020. The Effect of Activity Ratio on Profitability at PT. Indofood Sukses Makmur 2016-2020. The Effect of Working Capital and Activity Ratio on Profitability at PT. Indofood Sukses Makmur 2016-2020. The type of research used in this study is associative which aims to determine the effect of the independent variable on the dependent variable and how closely the influence or relationship of two or more variables. This study uses secondary and empirical data. The analytical tool used is multiple regression analysis. The results of the study state that working capital has no significant effect on profitability, working capital is proven to significantly affect profitability, meaning that it is able to provide a real positive influence in increasing profitability.